Of books and bagpipes - Shelton, Paige (Shelton, Paige. Scottish bookshop mystery series., 2017)
"Delaney Nichols has settled so comfortably into her new life in Edinburgh that she truly feels it's become more home than her once beloved Kansas. Her job at the Cracked Spine, a bookshop that specializes in rare manuscripts as well as other sundry valuable historical objects, is everything she had dreamed, with her new boss, Edwin MacAlister, entrusting her more and more with bigger jobs. Her latest task includes a trip to Castle Doune, a castle not far out of Edinburgh, to retrieve a hard-to-find edition of an old Scottish comic, an "Oor Wullie," in a cloak and dagger transaction that Edwin has orchestrated. While taking in the sights of the distant Highlands from the castle's ramparts, Delaney is startled when she spots a sandal-clad foot at the other end of the roof. Unfortunately, the foot's owner is very much dead and, based on the William Wallace costume he's wearing, perfectly matches the description of the man who was supposed to bring the Oor Wullie. As Delaney rushes to call off some approaching tourists and find the police, she comes across the Oor Wullie, its pages torn and fluttering around a side wall of the castle. Instinct tells her to take the pages and hide them under her jacket. It's not until she returns to the Cracked Spine that she realizes just how complicated this story is and endeavors to untangle the tricky plot of why someone wanted this man dead, all before getting herself booked for murder"--